Bayesian probability updates using sampling/importance resampling: Applications in nuclear theory - Jiang, Weiguang; Forssén, Christian (Frontiers in Physics, 2022)
We review an established Bayesian sampling method called sampling/importance resampling and highlight situations in nuclear theory when it can be particularly useful. To this end we both analyse a toy problem and demonstrate realistic applications of importance resampling to infer the posterior distribution for parameters of ΔNNLO interaction model based on chiral effective field theory and to estimate the posterior probability distribution of target observables. The limitation of the method is also showcased in extreme situations where importance resampling breaks.